Internal brace augmentation reconstruction versus standard anterior cruciate ligament reconstruction: a randomised controlled clinical trial study protocol - Xu Liu; Di Liu; Yusheng Li; Wenhao Lu; Zijun Cai; Linyuan Pan; Wenqing Xie; Hongfu Jin; Wenfeng Xiao (BMJ Open)
Introduction Anterior cruciate ligament (ACL) rupture is one of the most common knee injuries in sports, and the gold standard for treating ACL rupture is tendon graft reconstruction. Internal brace technology is being used nowadays for ligament repair; however, more relevant in vivo clinical evidence is required for using internal brace technology in ACL reconstruction (ACLR). We conducted a randomised controlled trial to investigate the clinical efficacy of internal brace technology in ACLR.Methods and analysis This randomised, parallel-controlled trial included patients with ACL rupture who underwent inpatient surgery at the Department of Orthopaedics, Xiangya Hospital, Central South University. Random number table method was used to assign the participants to either the test or the control group. The test group underwent ACLR using the internal brace technique, whereas the control group underwent standard ACLR. Uniform postoperative rehabilitation protocol was used for both the groups. Patient-reported outcomes included preoperative baseline and postoperative recovery at 1, 3, 6, 12 and 24 months. The primary outcome was International Knee Documentation Committee function from baseline (ACL rupture) to 6 months postoperatively. Secondary outcomes included (1) other patient outcome reporting metrics, Lysholm knee score, Knee Injury and Osteoarthritis Outcome Score and Visual Analog Scale; (2) the use of Kneelax3 knee stabiliser to assess knee stability; (3) occurrence of adverse events, such as graft refraction or symptomatic instability, postoperative infection and contralateral injury and (4) magnetic resonance images at 12 and 24 months after ACLR.Ethics and dissemination This trial was approved by the Medical Ethics Committee of the Xiangya Hospital of Central South University on 26 October 2021. Data will be published in peer-reviewed journals and presented at national and international conferences.Trial registration number ChiCTR2200057526.